The problem of the compatibility of bitumen sheets for the reconstruction and ehabilitation of roofs - Plachý Jan (MATEC Web of Conferences, 2017)
During the renovation of flat roofs, the waterproofing layer is often repaired locally rather than completely replaced. When making such repairs, it is very important to know whether the proposed bitumen sheets are compatible in order to prevent delamination and the release of the joints. This paper deals with the determination of the resistance of bitumen sheet joints against peeling when combined with different bitumen materials. On the basis of the described test methodology it was possible to determine whether the selected bitumen materials were compatible with bitumen sheets. As part of the experiments, modified bitumen sheets with plastomers (PO), oxidized bitumen (OX), and elastomers (SBS), were tested.